The Behavior of Real Interest Rates in Exchange-Rate Based Stabilization Programs - Agenor, Pierre-Richard (IMF Working Papers; Working Paper, 1994)
This paper examines the behavior of real interest rates in exchange-rate based stabilization programs. The analysis is based on a model with imperfect capital mobility and optimizing agents. A permanent reduction in the devaluation rate is first shown to have an ambiguous effect on real interest rates on impact. The analysis is then extended to consider a stabilization program characterized by an initial reduction in the rate of devaluation of the nominal exchange rate, and the announcement of a future increase in income taxes. The impact effect on real interest rates is shown to depend upon the degree of credibility of the announcement. Real interest rates may fall if agents do not believe that taxes will be raised, and rise if the future tax reform is sufficiently credible.